2013
DOI: 10.5172/ser.2013.20.1.55
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory investigation into voluntary employee turnover and retention in small businesses

Abstract: Given the scant research on turnover and retention in small businesses, this study addresses the questions: What factors influence voluntary employee turnover in small businesses and how do owner-managers retain key employees? Data were collected via semi-structured interviews with eight owner-managers and seven employees from ten Perth-based small businesses. The findings suggest that relationship conflict, limited career prospects, and unsolicited work roles and responsibilities were amongst the common reaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 5 publications
1
28
1
3
Order By: Relevance
“…Another research carried out by Mam and Mace (2010) focused on the impact of job design on employees' performance. Another research done by Gialuisi (2012) focused on Voluntary employee turnover and retention practices. There is a little empirical evidence pointing at the relationship between work design and employees' retention, particularly in the developing nations, South Africa included (Cappelli, 2000;Cole 2000;and Accenture, 2001).…”
Section: Career Management Practices: a Focus On Work Designmentioning
confidence: 99%
“…Another research carried out by Mam and Mace (2010) focused on the impact of job design on employees' performance. Another research done by Gialuisi (2012) focused on Voluntary employee turnover and retention practices. There is a little empirical evidence pointing at the relationship between work design and employees' retention, particularly in the developing nations, South Africa included (Cappelli, 2000;Cole 2000;and Accenture, 2001).…”
Section: Career Management Practices: a Focus On Work Designmentioning
confidence: 99%
“…Because knowledge and skills could degrade if not utilized(Bickerton, Miner, Dowson and Griffin, 2015), SME employees are less likely to leave because staying promotes effective utilisation of their skills. As employees develop various job skills through participation in varied and diverse roles, they may find it difficult to leave their job because leaving will be associated with giving up these job-related resources(Gialuisi and Coetzer, 2013;Storey, 1994;De Lange et al, 2008). Drawing on these arguments we propose that:…”
mentioning
confidence: 99%
“…Additionally, the aspect of job embeddedness describing how the newcomer fits with the organization or workgroup [16] reaffirms the idea that the relationship between the newcomer and the mentor impacts satisfaction described by one of our participants. Finally, the negative effect of unmet industry expectations on satisfaction reaffirms conclusions of research over the last two decades [14], [18].…”
Section: Satisfactionsupporting
confidence: 82%
“…Cloutier et al [1] noted the impact that innovative work has on newcomers, while Susomrith and Coetzer [5] found that employees often consider a high workload a barrier to training and development. While it is clear from both the results of this study and previous research that the clarity, difficulty, and amount of work play an important role in satisfaction and retention, the variety of tasks was previously only emphasized in small businesses [14]. In our research finding, task variety plays an important role in retention.…”
Section: Retentioncontrasting
confidence: 43%